Persistent neuropsychiatric symptoms after COVID-19: a systematic review and meta-analysis - Badenoch, J; Rengesamy, E; Watson, C; Jansen, K; Chakraborty, S; Sundaram, R; Hafeez, D; Burchill, E; Saini, A; Thomas, L; Cross, B; Hunt, C; et al. (Oxford University Press, 2021)
The nature and extent of persistent neuropsychiatric symptoms after COVID-19 are not established. To help inform mental health service planning in the pandemic recovery phase, we systematically determined the prevalence of neuropsychiatric symptoms in survivors of COVID-19. For this pre-registered systematic review and meta-analysis (PROSPERO ID CRD42021239750) we searched MEDLINE, EMBASE, CINAHL and PsycINFO to 20th February 2021, plus our own curated database. We included peer-reviewed studies reporting neuropsychiatric symptoms at post-acute or later time-points after COVID-19 infection, and in control groups where available. For each study a minimum of two authors extracted summary data. For each symptom we calculated a primary pooled prevalence using generalised linear mixed models. Heterogeneity was measured with I 2. Subgroup analyses were conducted for COVID-19 hospitalisation, severity, and duration of follow-up. From 2,844 unique titles we included 51 studies (n=18,917 patients). The mean duration of follow-up after COVID-19 was 77 days (range 14-182 days). Study quality was most commonly moderate. The most prevalent neuropsychiatric symptom was sleep disturbance (pooled prevalence=27·4% [95%CI 21·4-34·4%]), followed by fatigue (24·4% [17·5-32·9%]), objective cognitive impairment (20·2% [10·3-35·7%]), anxiety (19·1%[13·3-26·8%]), and post-traumatic stress (15·7% [9·9-24·1%]). Only two studies reported symptoms in control groups, both reporting higher frequencies in COVID-19 survivors versus controls. Between-study heterogeneity was high (I 2=79·6%-98·6%). There was little or no evidence of differential symptom prevalence based on hospitalisation status, severity, or follow-up duration. Neuropsychiatric symptoms are common and persistent after recovery from COVID-19. The literature on longer-term consequences is still maturing, but indicates a particularly high prevalence of insomnia, fatigue, cognitive impairment, and anxiety disorders in the first six months after infection.